Effects of Marathon Running on Cognition and Retinal Vascularization: A Longitudinal Observational Study - Roeh, Astrid; Schoenfeld, Julia; Raab, Raffaela; Landes, Viola; Papazova, Irina; Haller, Bernhard; Strube, Wolfgang; Halle, Martin; Falkai, Peter; Hasan, Alkomiet; Scherr, Johannes (Medicine and science in sports and exercise, 2021)
Introduction Physical activity has beneficial effects on both cardiovascular and neurocognitive parameters, and these two modalities are known to interact at rest. However, findings on their interaction during exercise are inconclusive. Purpose Therefore, this longitudinal study aimed to investigate the effects of different forms of exercise (training period, marathon race, and recovery period) on both parameters and their interaction. Methods We included 100 marathon runners (MA) (mean ± SD age = 43.6 ± 10.0 yr, 80 males) and 46 age- and sex-matched sedentary controls (SC, for baseline comparison). Over the 6-month study period with six visits (12 and 2 wk before the marathon; immediately, 24 h, 72 h, and 12 wk after the marathon), we assessed cognitive parameters by evaluating the 1- to 3-back d prime, the d2 task, and the Trail Making Tests A (TMT A) and B (TMT B), and the retinal vessel parameters by assessing arteriolar-to-venular ratio (AVR), central retinal arteriolar equivalent (CRAE), and central retinal venular equivalent (CRVE). Results In the long-term analysis, 3-back d prime correlated positively with AVR (P = 0.024, B = 1.86, SE = 0.824) and negatively with CRVE (P = 0.05, B = -0.006, SE = 0.003), and TMT B correlated negatively with CRAE (P = 0.025, B = -0.155, SE = 0.069), even after correcting for age and systolic blood pressure as possible confounders. Acute effects were inconsistent with maximal cognitive improvement 24 h after the marathon. AVR was significantly smaller in SC compared with MA. Conclusion Chronic exercise seems to prime the central nervous system for acute, intensive bouts of exercise. Our findings indicate a possible relationship between cognitive performance in high-demand tasks and retinal vasculature and support the idea of a neuroplastic effect of exercise.
CRIS-Team Scopus Importer:2023-03-08
Keywords: ARTERIOLAR-TO-VENULAR RATIO; CONCENTRATION; EXERCISE; RETINAL VESSEL; WORKING MEMORY